Second Five Year Plan District Plan 1956-1961 Srikakulam District - Planning Commission (Planning Commission, 1956)
With a view to increase agricultural production to the maximum extent possible, a number of schemes relating to agriculture have been proposed in the Second Five Year Plan. For implementing the various schemes included in the Plan, additional supervisory staff (Technical) and other ministerial staff is essential both at the State Headquarters as well as in the districts. It is therefore proposed to employ one District Agricultural Officer along with the required ministerial staff in each district of Andhra region towards which a provision of Rs. 10.69 lakhs has been made in the Second Plan.
Planning & Development Department Andhra Pradesh